2003
DOI: 10.1097/01.asn.0000093255.56474.b4
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Bone Loss in Renal Transplant Recipients with Vitamin D

Abstract: Abstract. Very rapid bone loss, osteopenia, and osteoporosis have been documented in the first 6 to 12 mo after renal transplantation. Investigated was the effect of treatment with active vitamin D on the prevention of posttransplantation bone loss. Forty adult men who were recent renal transplant recipients were enrolled onto the study. Patients were randomized into two groups: group 1 received daily alfacalcidol 0.5 g by mouth, and group 2 (control) received placebo. Every patient in both groups received dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 28 publications
3
23
1
2
Order By: Relevance
“…Consistently with these findings, our group have found that in patients randomized immediately after cardiac transplantation to 32000 IU/week of oral calcidiol for 18 months, lumbar spine BMD increased 5%, whereas those who received cyclical etidronate or nasal calcitonin, showed decreases in spine BMD (Garcia-Delgado et al, 1997). Also, alfacalcidol therapy has been associated with an increase in BMD or prevention of additional bone loss in renal (El-Agroudy et al, 2003) and cardiac recipients ( Van Cleemput et al, 1996).…”
Section: Calcidiol (25-hydroxivitamin D) and Alfacalcidol (1-hydroxisupporting
confidence: 66%
“…Consistently with these findings, our group have found that in patients randomized immediately after cardiac transplantation to 32000 IU/week of oral calcidiol for 18 months, lumbar spine BMD increased 5%, whereas those who received cyclical etidronate or nasal calcitonin, showed decreases in spine BMD (Garcia-Delgado et al, 1997). Also, alfacalcidol therapy has been associated with an increase in BMD or prevention of additional bone loss in renal (El-Agroudy et al, 2003) and cardiac recipients ( Van Cleemput et al, 1996).…”
Section: Calcidiol (25-hydroxivitamin D) and Alfacalcidol (1-hydroxisupporting
confidence: 66%
“…De Sevaux et al (65) reported a 6-mo randomized study of 113 patients with ␣-calcidiol plus calcium that showed, as in the previous study, decreased bone loss at lumbar spine and femoral neck when compared with untreated control subjects. El-Agroudy et al (66), in another study with 40 male patients who were randomly assigned to ␣-calcidiol plus calcium or placebo, demonstrated that the bone loss that occurred during the first year after renal transplantation could be prevented by ␣-calcidiol. This same group in a recent report randomly assigned 60 adult male patients to placebo, ␣-calcidiol, oral alendronate, or intranasal salmon calcitonin and showed that all treatment groups demonstrated improvement in BMD at all sites, with decreased BMD in the control group (67).…”
Section: Use Of Vitamin D Metabolitesmentioning
confidence: 99%
“…We chose a dosage of 0.25 g twice daily on the basis of previous renal transplant studies (23,24) and studies that used calcitriol to prevent loss of BMD in other solid-organ transplants (25,26). Some subsequent renal transplant studies have used similar regimens (17,27).…”
Section: Discussionmentioning
confidence: 99%